2011
DOI: 10.1063/1.3571448
|View full text |Cite
|
Sign up to set email alerts
|

Role of ZrO2 incorporation in the suppression of negative bias illumination-induced instability in Zn–Sn–O thin film transistors

Abstract: Thin film transistors (TFTs) with In and Ga-free multicomponent Zn–Sn–Zr–O (ZTZO) channel layers were fabricated using the cosputtering approach. The incorporation of ZrO2 into the Zn–Sn–O (ZTO) films increased the contact resistance, which led to the degradation of the transport properties. In contrast, the threshold voltage shift under negative bias illumination stress (NBIS) was largely improved from −12.5 V (ZTO device) to −4.2 V (ZTZO device). This improvement was attributed to the reduction in the oxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
41
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 23 publications
2
41
0
Order By: Relevance
“…15 The ionized V O 2þ charges would be accumulated at the channel/gate dielectric interface upon the application of NBS and hence exhibits a large negative V TH shift. 16 This assumption is well consistent with the increased DSS value of TFT-A and TFT-C under NBS at 60 C, as shown in Figs. 4(c) and 4(d), suggesting the creation of defect states at the channel/gate dielectric interface or in the channel layer.…”
supporting
confidence: 76%
See 2 more Smart Citations
“…15 The ionized V O 2þ charges would be accumulated at the channel/gate dielectric interface upon the application of NBS and hence exhibits a large negative V TH shift. 16 This assumption is well consistent with the increased DSS value of TFT-A and TFT-C under NBS at 60 C, as shown in Figs. 4(c) and 4(d), suggesting the creation of defect states at the channel/gate dielectric interface or in the channel layer.…”
supporting
confidence: 76%
“…16 Fig. 6(c) shows the XPS O1s spectra of a bare HfO 2 film as reference, which also exhibited similar O1s peaks approximately at the same binding energies as observed in case of ZnO film.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…The centre of the peak (I) located at 531.2 eV may be attributed to a combination of Cr 2 O 3 and MoO 2 , since very small chemical shifts between them are difficult to distinguish among those metal oxides by core level XPS. The peak (II) at 532.6 eV arises from the OH À ions and bound water in the surface film, which may be the adsorbed OH À impurities on the sample surface from the ambient atmosphere [44,45]. The peak (III) at 533.0 eV can be attributed to the contribution from water (H-O-H) or to the Si-O bond corresponding to silicon oxides [46].…”
Section: X-ray Photoelectron Spectroscopy Analysismentioning
confidence: 99%
“…The researchers suggested that high postannealing (300°C) treatment of a-GaSnZnO TFTs produced better electrical performance and stability than those of a-IGZO TFTs due to the Ga 3+ and Sn 4+ ions. There have been many similar demonstrations to date involving Si, Al, Zr, Hf, Ga, and Sn with InZnO and ZnSnO matrices, aimed at improving electrical performance (e.g., μ fe and stability) [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52].…”
Section: Multicomponent Oxide Semiconductorsmentioning
confidence: 99%